Component and antibacterial activity of crystal fraction from Zingiber zerumbetessential oil - Sri Mulyani (Indonesian Journal of Pharmacy, 2010)
The  aims  of  the  study  was  to  determine  of  the  crystal  fraction  from Zingiber  zerumbet essential  oils.  The  components  examination  was  performed by  GC-MS  method  using  the  solvent  n-hexane  and  anti bacterial  activity  was tested  against  Staphylococcus  aureus ATCC  25923  and  Escherichia  coli ATCC 35218  using  agar  diffusion  method  with  coconut  oil  solvent.  The  components that  can  be  identified  are  α-humulene,  caryophyllene  oxide,  β-selinene, and zerumbone. Crystal fraction solution able to inhibit of S. aureusATCC 25923 at  the  concentration  25  %  and  up  to  50  %  has  not  been  able  to  inhibit  E.  coli ATCC 35218.Key words : Zingiber zerumbet, Lempuyang gajah, Crystal fraction, anti-bacterial